Effect of microporous membrane properties and operating conditions on particle retention: Measurements and model studies. Issue 6 (12th April 2016) - Ostwal, Mayur; Lu, Xiaoyun; Beuscher, Uwe; Pellegrino, John
ABSTRACT: Depth filtration with microporous membranes has been modelled by extending upon previous approaches of Polyakov [1–4] to incorporate pore size distribution, tortuosity, and cake buildup. The model-forecasts were benchmarked against filtration measurements performed with colloidal particles using three very different commercial membrane morphologies with the same nominal average pore size. The critical flux for each membrane was determined by a standard flux-stepping method. Particle retention and permeance were studied under constant flux or transmembrane pressure test conditions. Comparison of the forecast results with data shows reasonable qualitative agreement, but the results are very sensitive to the measurement uncertainties of the various properties.